Effect of dissimilar metal welding on corrosion behavior of low carbon steel and 316L stainless steel - Amirool Bismie Abu Bakar, 1983- author; Esah Hamzah; Fakulti Kejuruteraan Mekanikal (2014)
Thesis (Sarjana Kejuruteraan (Kejuruteraan Bahan)) - Universiti Teknologi Malaysia, 2014